Gastroenteropancreatic Neuroendocrine Tumors: Hormonal Treatment Updates - Khagi, Simon; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
Gastroenteropancreatic neuroendocrine tumors are a heterogeneous group of carcinomas that remain difficult to treat with conventional cytotoxic regimens. The 2014 American Society of Clinical Oncology (ASCO) Gastrointestinal Cancers Symposium brought us new insights into the management of gastroenteropancreatic neuroendocrine tumors. The focus of this review will serve to highlight specific Abstracts (#268 and #273) that help shed light on a novel, targeted means of treating gastroenteropancreatic neuroendocrine tumors. Image: Carcinoid tumor of the small bowel (credit: Ed Uthman)